2017
DOI: 10.1111/tme.12492
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the blood supply in China during 2012–2014

Abstract: The blood product supply in China is steadily increasing. Blood centres in China continue to face challenges regarding their ability to provide a sufficient blood supply in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In underdeveloped and sparsely populated western China, which has 71% of China’s land area but only 28% of its population, 15 life expectancy is below the national average of 76 years 16 . A national survey in 2012–2014 also reported large regional variations in the ability of blood banks to supply blood 17 …”
Section: Introductionmentioning
confidence: 99%
“…In underdeveloped and sparsely populated western China, which has 71% of China’s land area but only 28% of its population, 15 life expectancy is below the national average of 76 years 16 . A national survey in 2012–2014 also reported large regional variations in the ability of blood banks to supply blood 17 …”
Section: Introductionmentioning
confidence: 99%
“…However, in these countries, most of the PCs transfused involve apheresis PLTs (97.23% SDPs, 2.77% RDPs), while the opposite is true in Greece (91.2% RDPs, 9.8% SDPs), as only 13 out of the 21 hospitals in the study have the necessary equipment and the expertise to produce PCs by apheresis. [ 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) suggested that, to meet a country's blood need sufficiently, the voluntary unpaid blood donation rate should be 10‰ to 30‰ [1]. Although the Chinese blood donation rate reached 11‰ in 2019 (up to the minimum standard [2]), it remains relatively low compared to the national average level [3,4]. Because China is still one of the countries with a blood supply shortage, fostering and retaining more blood donors have become an urgent problem requiring a solution.…”
Section: Introductionmentioning
confidence: 99%